An 8-Item Short Form of the Inventory of Dimensions of Emerging Adulthood (IDEA) Among Young Swiss Men. (June 2015) - Baggio, Stéphanie; Iglesias, Katia; Studer, Joseph; Gmel, Gerhard
Emerging adulthood is a period of life transition, in which youths are no longer adolescents but have not yet reached full adulthood. Measuring emerging adulthood is crucial because of its association with psychopathology and risky behaviors such as substance use. Unfortunately, the only validated scale for such measurement has a long format (Inventory of Dimensions of Emerging Adulthood [IDEA]—31 items). This study aimed to test whether a shorter form yields satisfactory results without substantial loss of information among a sample of young Swiss men. Data from the longitudinal Cohort Study on Substance Use Risk Factors were used ( N = 5, 049). IDEA, adulthood markers (e.g., parenthood or financial independence), and risk factors (i.e., substance use and mental health issues) were assessed. The results showed that an 8-item, short-form scale (IDEA-8) with four factors (experimentation, negativity, identity exploration, and feeling in between) returned satisfactory results, including good psychometric properties, high convergence with the initial scale, and strong empirical validity. This study was a step toward downsizing a measure of emerging adulthood. Indeed, this 8-item short form is a good alternative to the 31-item long form and could be more convenient for surveys with constraints on questionnaire length. Moreover, it should help health care practitioners in identifying at-risk populations to prevent and treat risky behaviors.